Enhancement of cement properties by means of in situ grown nanoparticles. (20th November 2020) - Mehairi, Ahmed G.; Husein, Maen M.
Graphical abstract: Highlights: Nanoparticles were synthesized within the cement slurry as it hydrates using three methods. The impact of nanoparticle dispersion within the cement matrix was investigated. Significant enhancement in compressive strength, fatigue resistance, porosity and permeability was achieved. The in situ prepared nanoparticles outperformed commonly used commercial nanoparticles. Tensile strength decreased with nanoparticles owing to their effect on crystal growth. Abstract: Inclusion of nanoparticles (NPs) into oil field cement improves key cement properties. Nevertheless, large-scale application of NPs suffers from high cost and lack of proper dispersion of commercial NPs. This work develops easy-to-scale, field-applicable methods to grow NPs within cement slurries starting from inexpensive water-soluble precursors. Three methods for preparing CaSO4, CaCO3 and Fe(OH)3 NPs are presented. Results showed that Fe(OH)3 NPs induced the highest increase in compressive strength, outperforming commercial NPs. Triaxial tests showed that the Fe(OH)3 NPs enhanced cured cement durability and resistance to fatigue. Moreover, Fe(OH)3 NPs led to significant reductions in porosity and permeability.